Nexus between financial development and Sustainable Development Goals (SDGs). European Union perspective - Zioło, Magdalena; Spoz, Anna; Szaruga, Elżbieta (Technological and Economic Development of Economy, 2025)
In environmental, social, and governance (ESG) risk conditions, implementing Sustainable Development Goals (SDGs) becomes a key priority. This involves not only direct financing but also establishing a support system through sustainable financial products and services, supported by the development of financial markets, especially in terms of sustainability. Financial development varies across countries, prompting an examination of the relationship between the SDGs and financial development in the European Union countries. 27 countries were studied from 2008 to 2021 using the Financial Development Index (FDI) and 55 indicators from the SDGs database. Panel data analysis was conducted, utilizing geostatistics and econometrics, including the cartogram method, descriptive statistics, dynamics, relative growth indicators, and panel unit root tests. The analysis revealed that financial development expressed by the immediate and delayed FDI is the Granger cause of shaping the SDGs. The most robust relationships were diagnosed for FDI and SDG2, SDG5, SDG8, SDG11, SDG12, and SDG16. The article makes an original contribution to research because, to the best of the authors’ knowledge, no similar research on FDI and SDGs has been conducted so far, and the research results may constitute a basis for authorities influencing FDI and SDGs.First published online 02 April 2025